2013
DOI: 10.1136/bmjopen-2012-002298
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress mediates the association between daytime sleepiness and consumption of sweetened products: cross-sectional findings in a Catholic Middle-Eastern Canadian community

Abstract: ObjectiveTo examine the associations between consumption of sweetened products, daytime sleepiness (DS) and psychological distress (PD) in a Catholic Middle-Eastern Canadian community, and to test the hypothesis that the association between DS and consumption of sweetened products is mediated by PD.DesignA cross-sectional study.SettingA Catholic Middle-Eastern Canadian community.Participants186 men and women aged between 18 and 60 years.Primary and secondary outcome measuresSweetened product consumption was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…Like poor sleep quality, insufficient sleep also results in poor dietary behaviors [ 19 , 20 , 21 , 55 , 56 , 57 , 58 , 59 , 60 ]. This may be explained by the fact that, like poor sleep quality, insufficient sleep also amplifies the brain’s reward system [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like poor sleep quality, insufficient sleep also results in poor dietary behaviors [ 19 , 20 , 21 , 55 , 56 , 57 , 58 , 59 , 60 ]. This may be explained by the fact that, like poor sleep quality, insufficient sleep also amplifies the brain’s reward system [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hedonic motivation to eat has been suggested as another promising explanation in recent studies. Moubarac et al (35) showed that the relation between daytime sleepiness and sweetened-food consumption was mediated by psychological distress, possibly suggesting that individuals with psychological distress are selecting energy-dense food items as a way to alleviate their stresses and improve their moods or increase their energy levels (31). Moreover, several studies have reported an increase in brain sensitivity toward a food-related reward (e.g., unhealthy food options) after sleep restriction (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…mood). Interestingly, a recent study reported that psychological distress mediates the association between daytime sleepiness and the consumption of sweetened products in adults [55]. One explanation in support of this mediating model is that individuals who experience daytime sleepiness may consume energy-dense foods to upgrade their energy level or to alleviate their negative mood or psychological distress.…”
Section: Accepted Manuscriptmentioning
confidence: 93%